2014
DOI: 10.1002/cctc.201402082
|View full text |Cite
|
Sign up to set email alerts
|

Induced Chirality in a Metal–Organic Framework by Postsynthetic Modification for Highly Selective Asymmetric Aldol Reactions

Abstract: A straightforward synthetic route to chiral metal-organic frameworks is proposed that relies on an acid-base interaction between an acid linker and a chiral primary amino acid derived diamine organocatalyst. High ee values for the aldol condensation of linear ketones and aromatic aldehydes are reported with this heterogeneous catalyst. Three consecutive catalyst reuse experiments demonstrated that the majority of the activity was preserved, as was the enantioselectivity.Although organocatalysis with amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…There are several asymmetric catalysts based on homochiral MOFs, but their expensive synthesis combined with their catalytic performance, which is often lower than that obtained with analogous homogeneous catalysts, have hampered their practical use. Alternatively, an achiral MOF can be functionalized with a chiral molecule, which is a modular and cost‐efficient solution also employed in this work. Given that MOFs feature a high surface area and big pores, they can be used as additives in catalysis to adsorb big molecules .…”
Section: Methodsmentioning
confidence: 99%
“…There are several asymmetric catalysts based on homochiral MOFs, but their expensive synthesis combined with their catalytic performance, which is often lower than that obtained with analogous homogeneous catalysts, have hampered their practical use. Alternatively, an achiral MOF can be functionalized with a chiral molecule, which is a modular and cost‐efficient solution also employed in this work. Given that MOFs feature a high surface area and big pores, they can be used as additives in catalysis to adsorb big molecules .…”
Section: Methodsmentioning
confidence: 99%
“…CCOFs prepared in this way are only constructed via achiral blocks, but the spatial organization of them endowed frameworks with chirality property. This method is mature in the synthesis of chiral MOFs, [ 35 ] but there was only one report on the synthesis of CCOFs published by Cui's group in 2018. [ 36 ] The researchers prepared a series of imine‐linked CCOFs in the presence of ( R )‐ or ( S )‐1‐phenylethylamine as chiral inducers.…”
Section: Design and Synthetic Strategies Of Chiral Covalent Organic Fmentioning
confidence: 99%
“…Surprisingly, however, there are very few examples of direct, noncovalent immobilization of discrete catalysts inside MOFs. Positively charged metal complexes were successfully incorporated into negatively charged frameworks by ion exchange. , Basic organocatalysts were immobilized in acidic MOFs by acid–base reactions. , Recently, we have also shown that cationic olefin metathesis (OM) catalysts can be easily immobilized inside (Al)­MIL-101-NH 2 and (Al)­MIL-101 by simple physisorption from solution. Although in these two cases the catalysts were held inside the MOFs by only noncovalent forces, no leaching was observed even in relatively polar solvents, such as dichloromethane (DCM) and ethyl acetate (EA).…”
mentioning
confidence: 99%
“…The heterogenized catalysts thus obtained can be used even in very polar “green” solvents, such as i -PrOH and dimethyl carbonate (DMC), , without any appreciable leaching of Ru into the solution. Although this straightforward acid–base strategy has been used for the immobilization of various catalysts on conventional supports, to the best of our knowledge the only precedents for a similar approach in MOFs are limited to the two organocatalysts mentioned above. , An alternative approach toward robust immobilization of OM catalysts for use in “green” solvents is presented in an accompanying paper by Grela and co-workers …”
mentioning
confidence: 99%
See 1 more Smart Citation